Adolescent counselling psychology : theory, research and practice - Hanley, Terry; Humphrey, Neil.; Lennie, Clare (London : Routledge, 2013)
'Adolescent Counselling Psychology: Theory Research and Practice provides a thorough introduction to therapeutic practice with young people. As an edited text, it brings together some of the leading authorities on such work into one digestible volume. The text is divided into three major sections. The first provides a context to therapeutic work with young people. This outlines the historical background to such work, the types of settings in which individuals work and the allied professions that they will encounter. Following on from this, the second section introduces the psychology of adolescence and provides an overview of the research into youth counselling. Finally, the third section considers more applied issues. Initially the infrastructure of counselling services is discussed before moving on to reflect upon pluralistic therapeutic practice. To end, the ways in which outcomes may be assessed in such work are described. In covering such a wide territory this text acts as an essential resource to those working within the field of adolescent counselling. It provides a foundation to the work that individuals are undertaking in this arena and advocates that individuals enter into therapeutic work in a critically informed way. At the heart of such considerations is the need to utilise psychological theory alongside research findings to inform therapeutic decision making'--
Includes bibliographical references and index.
Keywords: Adolescent psychotherapy; Adolescence -- Counseling of; Counseling -- Methods; Adolescent psychology